Fluorinated PLGA Nanoparticles for Enhanced Drug Encapsulation and 19F NMR Detection. Issue 44 (24th July 2020) - Neri, Giulia; Mion, Giuliana; Pizzi, Andrea; Celentano, Wanda; Chaabane, Linda; Chierotti, Michele R.; Gobetto, Roberto; Li, Min; Messa, Piergiorgio; De Campo, Floryan; Cellesi, Francesco; Metrangolo, Pierangelo; et al.
Abstract: In the continuous search for multimodal systems with combined diagnostic and therapeutic functions, several efforts have been made to develop multifunctional drug delivery systems. In this work, through a covalent approach, a new class of fluorinated poly(lactic‐co‐glycolic acid) co‐polymers (F‐PLGA) were designed that contain an increasing number of magnetically equivalent fluorine atoms. In particular, two novel compounds, F3 ‐PLGA and F9 ‐PLGA, were synthesized and their chemical structure and thermal stability were analyzed by solution NMR, DSC, and TGA. The obtained F‐PLGA compounds were proven to form in aqueous solution colloidal stable nanoparticles (NPs) displaying a strong 19 F NMR signal. The fluorinated NPs also showed an enhanced ability to load hydrophobic drugs containing fluorine atoms compared to analogous pristine PLGA NPs. Preliminary in vitro studies showed high cell viability and the NP ability to intracellularly deliver and release a functioning drug. Abstract : New, multimodal, fluorinated poly(lactic‐co‐glycolic acid) co‐polymers (F‐PLGA) were obtained by a covalent approach. The fluorinated PLGA compounds were easily formulated to obtain stable and quite monodispersed nanoparticles (NPs), which showed an average diameter of about 80 nm and a sharp 19 F NMR signal. Moreover, the ability of NPs to act as drug nanocarriers and their therapeutic activity were proven. Overall, these fluorinated co‐polymers could be candidates for multimodal drug delivery, which can be tracked in vivo by 19 F MRI.